REKONSTRUKSI KONSEP KITĀBAH DAN ISYHĀD DI ERA BLOCKCHAIN: SEBUAH PENDEKATAN TAFSIR MAUDHŪ'I TERHADAP QS. AL-BAQARAH: 282 - Lutfi Hery Rahmawan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Reconstructing Kitābah and Isyhād in the Blockchain Era: A Thematic Exegesis Approach to QS. Al-Baqarah: 282 The rapid digitalization of the global financial architecture has precipitated a crisis of trust and a demand for a fundamental reinterpretation of asset protection instruments (hifdz al-māl) within Islamic economics. This study investigates the theological and functional compatibility between the divine command of debt recording (kitābah) and witnessing (isyhād) as stipulated in QS. Al-Baqarah: 282, vis-à-vis the emergence of Blockchain technology and Smart Contracts. Employing a qualitative methodology with a maudhu'i (thematic) exegesis approach integrated with a socio-technical analysis, this research challenges the conservative jurisprudential view that restricts kitābah to physical paper-based documentation. The findings demonstrate that the immutable, non-repudiable, and decentralized nature of Distributed Ledger Technology (DLT) constitutes the highest contemporary manifestation of kitābah, surpassing the security and integrity offered by traditional methods. Furthermore, this study proposes a radical paradigm shift in the epistemological understanding of isyhād, arguing that algorithmic consensus mechanisms (such as Proof-of-Work or Proof-of-Stake) qualify as "digital witnesses" that effectively eliminate human cognitive bias, negligence, and perjury. Consequently, the integration of Triple-Entry Accounting is proposed as a new, robust standard for Sharia accountability. This study concludes that the adoption of blockchain in Fintech is not merely a technical innovation for efficiency, but a theological imperative to ensure absolute transparency and eliminate uncertainty (gharar) in modern economic transactions.